Variability in the contribution of different life stages to population growth as a key factor in the invasion success of Pinus strobus - Münzbergová, Zuzana; Hadincová, Věra; Wild, Jan; Kindlmannová, Jana (PLoS One, 2013)
BACKGROUND: Despite the increasing number of studies attempting to model population growth in various organisms, we still know relatively little about the population dynamics of long-lived species that reproduce only in the later stages of their life cycle, such as trees. Predictions of the dynamics of these species are, however, urgently needed for planning management actions when species are either endangered or invasive. In long-lived species, a single management intervention may have consequences for several decades, and detailed knowledge of long-term performance can therefore elucidate possible outcomes during the management planning phase. METHODOLOGY AND PRINCIPAL FINDINGS: We studied the population dynamics of an invasive tree species, Pinus strobus, in three habitat types represented by their position along the elevation gradient occupied by the species. In agreement with previous studies on the population dynamics of long-lived perennials, our results show that the survival of the largest trees exhibits the highest elasticity in all of the studied habitats. In contrast, life table response experiments (LTRE) analysis showed that different stages contribute the most to population growth rates in different habitats, with generative reproduction being more important in lower slopes and valley bottoms and survival being more important on rock tops and upper slopes. CONCLUSIONS: The results indicate that P. strobus exhibits different growth strategies in different habitats that result in similar population growth rates. We propose that this plasticity in growth strategies is a key factor in the invasion success of the white pine. In all of the investigated habitats, the population growth rates are above 1, indicating that the population of the species is still increasing and has the ability to spread and occupy a wide range of habitats.
Keywords: borovice; ekosystém; Population Dynamics; zavlečené druhy; Švýcarsko; populační dynamika; Population Growth; Ecosystem; Switzerland; Pinus; Introduced Species; populační růst